Exploring The Controversy Over School Accreditation Standards In Shaping Public Perceptions Of National Education Quality - Sutriani; Mohamed Nor, Abdullah Shukri (JIEMAN: Journal of Islamic Educational Management, 2024)
This study examines the controversy of school accreditation standards in shaping public perceptions of the quality of national education at SMA Al-Hikmah Muncar Banyuwangi. This research uses qualitative methods, with data collection through observation, interviews and documentation. Data analysis used three model analysis techniques. The results show that there is a diversity of community perceptions of accreditation, which is influenced by various factors such as personal experience, socio-economic background and information obtained. In addition, three points emerged relating to the accreditation process at Al-Hikmah Muncar Banyuwangi High School, namely a too narrow focus on administrative aspects, lack of transparency, and limited stakeholder involvement. To improve the quality of education, this study suggests the need for a more comprehensive evaluation of the accreditation system.